2020
DOI: 10.5811/westjem.2020.5.46010
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Alerts in Emergency Departments: A Systematic Review of Accuracy and Quality Measure Impact

Abstract: Introduction For early detection of sepsis, automated systems within the electronic health record have evolved to alert emergency department (ED) personnel to the possibility of sepsis, and in some cases link them to suggested care pathways. We conducted a systematic review of automated sepsis-alert detection systems in the ED. Methods We searched multiple health literature databases from the earliest available dates to August 2018. Articles were screened based on abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…However, the in-hospital mortality for patients with sepsis present on admission, using the Sepsis-3 criteria for sepsis identification was similar to the previous epidemiologic result (13.5% in our study vs. 13.4% in previous study) [24]. Second, heterogeneity in study designs has been shown to hinder the comparison of performance among different models [18,27]. Therefore, we could hardly compare the performance of our model with previous models [50][51][52][53] because considerable heterogeneity was found among our study and previous studies, including the patient characteristics (e.g., all ED visits versus only ED admissions, with differences in sepsis prevalence), selecting predictors (e.g., vitals, lab test results versus text data from the EHR), the reference standard for sepsis (ICD coding versus the Sepsis-3 criteria), and diagnostic outcomes (e.g., sepsis versus severe sepsis and septic shock versus mortality).…”
Section: Study Limitationssupporting
confidence: 89%
See 2 more Smart Citations
“…However, the in-hospital mortality for patients with sepsis present on admission, using the Sepsis-3 criteria for sepsis identification was similar to the previous epidemiologic result (13.5% in our study vs. 13.4% in previous study) [24]. Second, heterogeneity in study designs has been shown to hinder the comparison of performance among different models [18,27]. Therefore, we could hardly compare the performance of our model with previous models [50][51][52][53] because considerable heterogeneity was found among our study and previous studies, including the patient characteristics (e.g., all ED visits versus only ED admissions, with differences in sepsis prevalence), selecting predictors (e.g., vitals, lab test results versus text data from the EHR), the reference standard for sepsis (ICD coding versus the Sepsis-3 criteria), and diagnostic outcomes (e.g., sepsis versus severe sepsis and septic shock versus mortality).…”
Section: Study Limitationssupporting
confidence: 89%
“…The increasing availability of electronic health records (EHR) and advancing machine learning (ML) techniques has stimulated attempts to identify patient conditions through the automated analysis of medical records. Previous studies have shown that the ML approach can facilitate the detection of sepsis and septic shock [10,[16][17][18]. However, the clinical utility of these models in the emergency department (ED) setting remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis, a complex disease, characterized by a host’s dysfunctional response to infection that leads to life-threatening multiorgan dysfunction ( Dugar et al, 2020 ). Studies have found that the release of inflammatory cytokines, such as tumor necrosis factor (TNF-α) and interleukins (IL-1β and IL-6) increases, and promotes many immunopathological processes in sepsis, which are often referred to as “cytokines storm” ( Ono et al, 2018 ; Hwang et al, 2020 ). As the most common source of infection in patients with sepsis comes from the abdominal cavity, in recent years, the abdominal infection model has been gradually used as a commonly used animal model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Neither automated nor rule-based sepsis alerts in a systematic review conducted in 2020 showed any difference in mortality, nor were potential harms assessed. 21 Another systematic review in 2015 highlighted the danger of alert fatigue as many ICU patients can meet the SIRS criteria without being septic. 22 Therefore, other researchers have turned to developing device-based diagnostics that can be performed at the bedside.…”
Section: Introductionmentioning
confidence: 99%